120k views
5 votes
I need help in this one please

I need help in this one please-example-1
User Dsdsdsdsd
by
6.1k points

2 Answers

1 vote
The answer is -3. I had a lovely explanation to go with this, but unfortunately the filter will not allow me to post it and I'm not sure why. Sorry for the inconvenience.
User Emac
by
6.5k points
6 votes
For this case we have the following functions:

f (x) = x-2 g (x) = x ^ 2 - 7x - 9
The first thing we must do is perform the composition of functions.
We have then:

f (g (x)) = (x ^ 2 - 7x - 9) -2
Rewriting we have:

f (g (x)) = x ^ 2 - 7x - 11
We now evaluate the function for x = -1.
We have then:

f (g (-1)) = (-1) ^ 2 - 7 (-1) - 11
Rewriting we have:

f (g (-1)) = 1 + 7 - 11 f (g (-1)) = -3
Answer:
The function of f composed with g evaluated for x = -1 is given by:

f (g (-1)) = -3
option 2
User FirmView
by
6.1k points